Perturbation of biological processes with small molecule kinase inhibitors. (October 2022) - Li, Wenyang; Wang, Jue; Liang, Ruqi; Lei, Xiaoguang
Abstract: The reversible phosphorylation of substrates mediated by kinases and phosphatases affects their subcellular localization, catalytic activity, and/or interaction with other molecules. It is essential for signal transduction and the regulation of nearly all cellular processes, such as proliferation, apoptosis, metabolism, motility, and differentiation. Small molecule kinase inhibitors (SMKIs) have served as critical chemical probes to reveal the biological functions and mechanisms of kinases and their potential as therapeutic targets. In this review, we focused on a few novel SMKIs and their recent application in biological and preclinical studies to showcase how highly selective and potent SMKIs can be developed and utilized to propel the investigations on kinases and the biology behind.